Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lizy

\(\left\{{}\begin{matrix}y=20+x\\\dfrac{100}{x}-\dfrac{100}{20+x}=\dfrac{5}{6}\end{matrix}\right.\)

Nguyễn Lê Phước Thịnh
18 tháng 1 2024 lúc 21:45

ĐKXĐ: \(x\notin\left\{0;-20\right\}\)

\(\left\{{}\begin{matrix}y=20+x\\\dfrac{100}{x}-\dfrac{100}{20+x}=\dfrac{5}{6}\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\\dfrac{20}{x}-\dfrac{20}{x+20}=\dfrac{1}{6}\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\\dfrac{20x+400-20x}{x\left(x+20\right)}=\dfrac{1}{6}\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\\dfrac{400}{x\left(x+20\right)}=\dfrac{1}{6}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=x+20\\x\left(x+20\right)=2400\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\x^2+20x-2400=0\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\\left(x+60\right)\left(x-40\right)=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=x+20\\\left[{}\begin{matrix}x+60=0\\x-40=0\end{matrix}\right.\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}y=x+20\\x\in\left\{-60;40\right\}\end{matrix}\right.\)(nhận)

=>\(\left[{}\begin{matrix}\left\{{}\begin{matrix}x=-60\\y=x+20=-60+20=-40\end{matrix}\right.\\\left\{{}\begin{matrix}x=40\\y=x+20=60\end{matrix}\right.\end{matrix}\right.\)


Các câu hỏi tương tự
tranthuylinh
Xem chi tiết
tranthuylinh
Xem chi tiết
Sooun Lee
Xem chi tiết
Thanh Thanh
Xem chi tiết
Hồ Trần Yến Nhi
Xem chi tiết
gfdzdfa
Xem chi tiết
Xem chi tiết
Phạm Mạnh Kiên
Xem chi tiết
tranthuylinh
Xem chi tiết